2016
DOI: 10.1109/tie.2015.2499252
|View full text |Cite
|
Sign up to set email alerts
|

Application of Calorimetric Method for Loss Measurement of a SynRM Drive System

Abstract: Abstract-Synchronous reluctance motors (SynRMs) are gaining in popularity in industrial drives due to their permanent magnet-free, competitive performance and robust features. This paper studies the power losses in a 90 kW converter-fed SynRM drive by a calorimetric method in comparison of the traditional input-output method. After the converter and the motor were measured simultaneously in separate chambers, the converter was installed inside the large-size chamber next to the motor and the total drive system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Besides, the differences between the prices of the drive systems in the same rated power can be compensated by the lower energy cost. Recent studies, innovations, and also the need for higher efficiency and better performance support the prospect of more future widespread development of motor drive systems in the industry [12,93,94]. These parameters require more study in different areas that can be categorized as follows:…”
Section: Latest Developments Of Synrm Control Strategiesmentioning
confidence: 99%
“…Besides, the differences between the prices of the drive systems in the same rated power can be compensated by the lower energy cost. Recent studies, innovations, and also the need for higher efficiency and better performance support the prospect of more future widespread development of motor drive systems in the industry [12,93,94]. These parameters require more study in different areas that can be categorized as follows:…”
Section: Latest Developments Of Synrm Control Strategiesmentioning
confidence: 99%
“…The energy efficiency of an electric motor-drive system including a VSC and a synchronous reluctance motor is analyzed in [25] whereas in [26] a double chamber calorimeter with series chamber arrangement is introduced with a loss measurement accuracy below 1.5% of losses of the frequency converter in the loss range from 100 W to 400 W. The calorimeter efficiency uncertainty is analyzed to be very small, about 0.03%, and the power meter uncertainty with the inputoutput method 0.47% or 0.74% depending on the analysis method at the efficiency level of 97%. In [27], a new calorimetric loss measurement method is designed to implement a fast and accurate power loss measurement of WBG devices during the circuit operation.…”
Section: Bibliographical Reviewmentioning
confidence: 99%
“…And so, calorimeters, in the current climate serve as an alternate way of loss measurement that can verify the accuracy of input-output loss measurement in high efficiency devices, in situations of distorted waveforms and in verifying efficiency classes. Aarniovuori et al (2016) used calorimeters to measure the loss of SynRM and its drive separately and together, and it was found that the converter-fed losses of the SynRM obtained thus, and from the input-output method were quite close.…”
Section: Disadvantagesmentioning
confidence: 99%